Elaboración de un plan de manejo enfocado al manejo de la Boa (Boa constrictor constrictor) mediante el análisis socioambiental y económico en la comunidad Ayllu awuarina - Ledesma Ugsiña, Jessica Patricia (2015)
This research focuses on the illegal possession of wild species Boa constrictor (Boa constrictor), and the obvious exploitation of this reptile to generate income for the benefit of the families of the Kichwa community Awuarina Ayllu, located in the parish Misahuallí, Canton Tena, Napo province, activity is verified in our Amazon territory. To solve the above problem the social, economic and environmental aspects that have families in the community Ayllu Awuarina analyzed; the management cycle was characterized in captivity of the species Boa constrictor (Boa constrictor) and a management plan was proposed wildlife; applying methodology as surveys, expert interviews and site visits tenure wildlife of the area that handle this species in captivity. Data analysis showed that 75% of the community is dedicated to community tourism; 24% is dedicated to shamanism and 20% to take pictures with the Boa constrictor (Boa constrictor). 100% of hospitals surveyed were zoos; 50% indicate that this species is able to live for 11-20 years and according to the indicators determines the welfare of this species in captivity for 75% identified by the appearance of the skin. To contribute to the conservation of this species in captivity was developed center design and management tenure Ñucanchi Kausai with the respective wildlife management plan and the programs referred to function